Effective endovascular treatment of veins of Galen malformation in a child: A case study - Abdellah Ayoub, PhD; ETAKI Zakaria, MD; Rghioui Mounir, PhD; Moufid Faycal, PhD; Boutarbouch Mahjouba, PhD (Radiology Case Reports, 2025)
Vein of Galen aneurysmal malformation (VGAM) is a rare congenital arteriovenous anomaly characterized by abnormal connections between cerebral arteries and the vein of Galen. This case report details the presentation, diagnosis, and management of a 10-year-old boy from Gabon, who exhibited learning difficulties, macro crania, and generalized tonic-clonic seizures. A cerebral CT scan revealed an aneurysmal malformation of the ampulla of Galen with tri ventricular hydrocephalus, necessitating the placement of a peritoneal shunt. Upon referral to our facility, the patient underwent an angioMRI and malformative work-up, followed by an arteriogram confirming the diagnosis. The subsequent endovascular embolization procedure resulted in significant cognitive and radiological improvements, with no further seizures or signs of ischemia. This case underscores the importance of timely diagnosis and intervention in managing Vein of Galen aneurysmal malformation (VGAM), highlighting the efficacy of endovascular therapy.